THE ROLE OF THE INTERNATIONAL MONETARY FUND IN RESOLVING THE GLOBAL FINANCIAL CRISIS - MIHAI SPĂTARU-NEGURĂ (Challenges of the Knowledge Society, 2012)
In 2008-2009, the global economy experienced the worst financial crisis since the Great Depression in the 1930s, as it has been characterized. We consider that the current global financial crisis is a major challenge for the International Monetary Fund („IMF” or the „Fund”). The IMF has emerged as a powerful institutional force and has provided recomendations and analyses that have served as the basis of official action on several fronts. This paper discusses the potential roles the Fund may have in resolving the current global financial crisis.